Engineering a self-navigated MnARK nanovaccine for inducing potent protective immunity against novel coronavirus. (June 2021) - Wang, Yaling; Xie, Yuping; Luo, Jia; Guo, Mengyu; Hu, Xuhao; Chen, Xi; Chen, Ziwei; Lu, Xinyi; Mao, Lichun; Zhang, Kai; Wei, Liangnian; Ma, Yunfei; et al.
Highlights: Novel nanovaccine (comprises of RBD antigen and the manganese nanoadjuvant (MnARK)) induces potent humoral and cellular responses. Shown stronger neutralizing abilities against pseudovirus and coronavirus were shown with lower antigen dose and fewer injections. Co-delivery of RBD antigen and MnARK to lymph nodes (LNs) and strong activation of antigen presenting cells. Graphical Abstract: New nanovaccine that comprises of RBD and the manganese nanoadjuvant (MnARK) induces humoral and cellular responses. ga1 Abstract: Effective vaccines are vital to fight against the COVID-19 global pandemic. As a critical component of a subunit vaccine, the adjuvant is responsible for strengthening the antigen-induced immune responses. Here, we present a new nanovaccine that comprising the Receptor-Binding Domain (RBD) of spike protein and the manganese nanoadjuvant (MnARK), which induces humoral and cellular responses. Notably, even at a 5-fold lower antigen dose and with fewer injections, the MnARK vaccine immunized mice showed stronger neutralizing abilities against the infection of the pseudovirus (~270-fold) and live coronavirus (>8-fold) in vitro than that of Alum-adsorbed RBD vaccine (Alu-RBD). Furthermore, we found that the effective co-delivery of RBD antigen and MnARK to lymph nodes (LNs) elicited an increased cellular internalization and the activation of immune cells, including DCs, CD4 + and CD8 + T lymphocytes. Our findings highlight the importance of MnARK adjuvant in the design of novel coronavirus vaccines and provide a rationale strategy to design protective vaccines through promoting cellular internalization and the activation of immune-related pathways.